Hidden Valley Road [large type] : inside the mind of an American family - Kolker, Robert (Random House Large Print, 2020)
"Don and Mimi Galvin seemed to be living the American dream. After World War II, Don's work with the Air Force brought them to Colorado, where their twelve children perfectly spanned the baby boom. There was a script for a family like the Galvins--hard work, upward mobility, domestic harmony--and they all tried to play their parts. But behind the closed doors of the house on Hidden Valley Road was a far different reality: psychological breakdown, sudden shocking violence, and hidden abuse. By the mid-1970s, six of the ten Galvin boys, one after the other, were diagnosed with schizophrenia. And the other six children stood by, horrified, with no way of knowing whether they would be next. What took place on Hidden Valley Road was so extraordinary that the Galvins became one of the first families to be studied by the National Institute of Mental Health. In a tour de force of narrative nonfiction, award-winning journalist Robert Kolker...tells the intimate story of the Galvins alongside the epic tale of science's quest to uncover the true nature of a mystifying disease. Each mentally ill brother emerges as wholly individual, with remarkably different expressions of the same disorder. The two youngest Galvins, the only girls, are indelible characters: best friends, both victimized by their brothers, who make sharply different choices about how to cope. The Galvins' story crests in a breakthrough that, thanks to their unique DNA, offers hope of eliminating schizophrenia forever."-- Back cover.